1991
DOI: 10.1007/bf00587826
|View full text |Cite
|
Sign up to set email alerts
|

CT and MR imaging of acute cerebellar ataxia

Abstract: An adult female showed mild cerebellar ataxia and CSF pleocytosis following an acute infection of the upper respiratory tract, and was diagnosed as having acute cerebellar ataxia (ACA). CT and MR appearances in the acute stage revealed moderate swelling of the cerebellum and bilaterally increased signal intensity in the cerebellar cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…We hypothesise that in most cases, the diagnosis of PCD is carried out at later stages of the disease, when the cerebellar atrophy has been established after an initial inflammatory response. Supporting this idea, we found close similarities between our case and the case of Shoji et al 8 with acute infectious cerebellar ataxia. In that case, the cerebellar oedema disappeared 1 month later, whereas in our case evolved to atrophy.…”
supporting
confidence: 90%
“…We hypothesise that in most cases, the diagnosis of PCD is carried out at later stages of the disease, when the cerebellar atrophy has been established after an initial inflammatory response. Supporting this idea, we found close similarities between our case and the case of Shoji et al 8 with acute infectious cerebellar ataxia. In that case, the cerebellar oedema disappeared 1 month later, whereas in our case evolved to atrophy.…”
supporting
confidence: 90%
“…[25] Inflammation of the cerebellum in childhood may be infectious, postinfectious or due to vaccines. [25][26][27][28][29][30][31][32][33][34][35] Infectious agents may also be varied. Some of the patients may be asymptomatic through infection or may display only mild symptoms.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35] Therefore, we aimed to determine the relationships of measles, mumps, rubella, cytomegalovirus (CMV), Ebstein-Barr Virus (EBV), HSV and VZV, which may all be agents of cerebellar inflammation, to ADHD. [25][26][27][28][29][30][31][32][33][34][35] As far as we are aware, no controlled studies on Turkish children and adolescents with ADHD to determine their status of immunity to viral agents have been conducted up to now.…”
mentioning
confidence: 99%
“…Some investigators have suggested the pathophysiology of acute cerebellar ataxia involves oedematous cerebellitis based on MRI4 and SPECT5 findings. In our case, no abnormalities were noted, possibly because the cerebellitis was mild as suggested by the clinical course.…”
Section: Discussionmentioning
confidence: 99%